Sub-Rectangular Tunnel Behavior under Seismic Loading - Van Vi Pham; Ngoc Anh Do; Daniel Dias (Applied Sciences, 2021)
Circular and rectangular tunnel shapes are usually chosen when excavating at shallow depths in urban areas. However, special-shaped tunnels such as sub-rectangular tunnels have recently been used to overcome some drawbacks of circular and rectangular tunnels in terms of low space utilization efficiency and stress concentration, respectively. In the literature, experimental studies as well as analytical and numerical models have been developed for the seismic analysis and vulnerability assessment of circular and rectangular tunnels since the early 1990s. However, knowledge gaps regarding the behavior of sub-rectangular tunnels under seismic loading remain and still need to be bridged. The present paper focuses on introducing a numerical analysis of sub-rectangular tunnels under seismic loading. The numerical model of sub-rectangular tunnels is developed based on the numerical analyses of circular tunnels validated by comparing well-known, analytical solutions. This paper aims to highlight the differences between the behavior of sub-rectangular tunnels compared with circular tunnels when subjected to seismic loadings. Special attention is paid to the soil–lining interface conditions. The influence of parameters, such as soil deformations, maximum horizontal acceleration, and lining thickness, on sub-rectangular tunnel behavior under seismic loading is also investigated. The results indicate a significant behavior difference between sub-rectangular and circular tunnels. The absolute extreme incremental bending moments for a circular tunnel (no-slip condition) are smaller than that for the corresponding full-slip condition. The absolute extreme incremental bending moments of sub-rectangular tunnels (no-slip condition) are, however, greater than the corresponding full-slip conditions.